Comparative study of new loquat varieties: Physico-chemical and phytochemical analyses - Vilhena, Nariane Q.; Salvador, Alejandra; Cháfer, Maria Teresa; Gil, Rebeca; Soler, Esteban; Bermejo, Almudena (ELSEVIER, 2025)
The present work performs a comparative study of 10 different loquat varieties to identify significant differences among varieties and categorize them based on their main physicochemical and phytochemical properties. For each variety, physicochemical properties (external and internal color, flesh firmness, soluble tannins, total soluble solids, titratable acidity) and the main phytochemical compounds (sugars, organic acids, vitamin C, phenolic compounds, carotenoids) were evaluated in fruit harvested at two commercial maturity stages. This study revealed significant differences in these characteristics among cultivars. Principal component analysis (PCA) allowed varieties to be grouped into three well-differentiated groups, especially in terms of total acidity, phenolic compounds and carotenoids. PCA also allow fruit quality attributes to be correlated with the main bioactive compounds and clearly separated the maturity stages for each cultivar. These results reveal the diversity of chemical composition and nutritional value of loquat fruits and provide valuable information on the commercial potential of new varieties. Moreover, this information is valuable for breeding programs, as cultivars with specific traits can be used as parent material for future crosses